Development of a Transformational Leadership Model for Principals at SD Negeri 126 Borong, Bulukumba Regency - Nur Afni; Abdul Wahid (South Sulawesi Education Development (SSED), 2023)
The principal's transformational leadership model at SD Negeri 126 Borong, Bulukumba Regency, will be tested for practicality and efficacy. This study examined SD Negeri 126 Borong, Bulukumba Regency principals and teachers. Research and development follows the ADDIE model, which has five steps: analysis, design, development, implementation, and evaluation (evaluation). Data was collected through observation, questionnaires, interviews, and documentation. A model development observation sheet, research instrument sheet, questionnaire on school principals and teachers' practicality and effectiveness, and documents on school principals' transformational leadership model implementation at SD Negeri 126 Borong, Bulukmba Regency are used in the research instrument. Data analysis is done using qualitative and quantitative methods. This research shows that the principal at SD Negeri 126 Borong, Bulukumba Regency can implement the transformational leadership model to mobilize all stakeholders to achieve school goals, such as improving the teaching and learning process, establishing a positive school learning direction and climate, and improving excellent service to achieve high academic achievement (learning outcomes). Based on observations of school principals implementing transformational leadership and questionnaire responses from principals and teachers, this model passed the practicality test. The effectiveness test results show that this model is effective in moving all stakeholders to achieve school goals, including improving teaching and learning, establishing a positive school learning direction and climate, and improving excellent service to achieve high student academic achievement (learning outcomes).